Carbon nanotubes as electronic mediators combined with Bi2MoO6 and g-C3N4 to form Z-scheme heterojunctions to enhance visible light photocatalysis. (22nd December 2021) - Wu, Hao; Meng, Fanming; Liu, Xingbing; Yu, Bo
Abstract: In this paper, Z-scheme Bi2 MoO6 /CNTs/g-C3 N4 composite photocatalysts were prepared through a simple hydrothermal method. The analysis was performed by XRD, FT-IR, SEM, EDS, TEM, HRTEM, XPS, BET, UV–Vis diffuse reflectance and PL spectrums. Various analyses show that CNTs not only act as excellent charge transfer bridges, but also enable a formation of the Z-scheme of charge transfer mechanism between Bi2 MoO6 and g-C3 N4 . This process not only effectively isolates electrons and holes, but also prolongs electron–hole pair lifetimes, resulting in a substantial improvement in the photocatalytic performance of the composite photocatalyst. Best photocatalytic degradation performance was shown by Bi2 MoO6 /CNTs/g-C3 N4 composite photocatalyst under simulated sunlight, while the composite photocatalyst still maintained extremely high degradation performance in cycling tests.